Beak and feather disease virus carriage by Knemidocoptes pilae in a sulphur‐crested cockatoo (Cacatua galerita). Issue 12 (28th November 2017) - Portas, T; Jackson, B; Das, S; Shamsi, S; Raidal, SR
Abstract : Background: This paper describes the pathology associated with psittacine beak and feather disease in a wild sulphur‐crested cockatoo with concurrent knemidocoptic mange, cestodiasis and mycotic encephalitis. Methods & Results: Large numbers of Knemidocoptes pilae Lavoipierre and Griffiths, 1951 (Acari: Epidermoptidae, Knemidokoptinae) were identified in affected skin associated with enhanced expression of beak and feather disease virus (BFDV) determined by immunohistochemistry. Also, BFDV antigen was demonstrated in high concentration in the gut and faecal sacs of mites, raising the possibility of ectoparasites as fomites and vectors of BFDV transmission. Large numbers of Raillietina spp. cestodes were present in the intestines. Within the brain there was a focally extensive region of necrosis and inflammation associated with branching, septate, pigmented hyphae consistent with zygomycete fungal infection. Conclusion: This case highlights the potential immunosuppressive effects of BFDV infection and its potential as a keystone pathogen in the Australian environment.